A Class of Unbounded Fourier Multipliers on the Unit Complex Ball - Pengtao Li; Jianhao Lv; Tao Qian (Abstract and Applied Analysis)
We introduce a class of Fourier multiplier operators Mb on n-complex unit sphere, where the symbol b∈Hs(Sω). We obtained the Sobolev boundedness of Mb. Our result implies that the operators Mb take a role of fractional differential operators on ∂𝔹.